Road Traffic Noise in Algeria: State Decisions Comprehensive Review - Boulemaredj Ali; Meribai Amine Mehdi (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Urban transportation system offers a major standard for measuring general operational efficiency of a city and its compliance with traffic laws. This research supports the latest Algerian government instructions, which focuses on the legislative aspect of road noise control mechanisms via a thorough analysis of the recently adopted State Decisions. Setif and Annaba, as well as Algiers and Blida cities, are enforcing the restriction of the presence of extremely noisy sports cars and motorcycles within urban and residential zones at night. This specific project is part of a more comprehensive set of preventative and repressive measures that have been deliberately designed to lower noise pollution and maintain public tranquillity. This research aims to support the enforcement of national noise control rules as well provide suggestions that are both financially feasible and helping to improve the management of noise problems connected to urban mobility.